Generalized Ghost Pilgrim Dark Energy in Brans–Dicke Theory - Prasanthi, Yetchena; Davuluri, Neelima (East European Journal of Physics, 2024)
This paper aims to investigate, how the Bianchi Type-V cosmological model can be solved using the generalized ghost pilgrim dark energy postulated by the Brans-Dicke theory of gravitation (Phys. Rev.124, 925 1961). To discover the answers, we rely on the assumptions of (i) the correlation between metric potentials and (ii) the exponential relationship between scale factor and scalar field. The generalized ghost pilgrim dark energy model has been found to be correlated with the polytrophic gas dark energy model. A few physical quantities have been used to explain the solutions’ physical behavior.